Program Peningkatan Kompetensi Konselor Melalui Analisis dan Pengubahan Tingkah Laku pada Siswa SMP Kota Malang - Henny Indreswari; Rizka Apriani; Riskiyana Prihatiningsih; Linka Latifany Falasifa Reidana; Alief Laili Budiyono (Universitas Negeri Malang, 2024)
Abstract: This community service project applies research findings on developing a model program to enhance the competencies of counselors through behavior analysis and modification for junior high school students in Malang City. The model is designed to provide training and guidance in implementing behavior analysis and modification programs for problematic student behaviors, as well as to offer recommendations and improvement guidelines. The training employs the Problem-Based Learning (PBL) method, following these procedures: (1) preparation, (2) implementation, (3) evaluation and follow-up, and (4) reporting. The target of the counselor competency enhancement program consists of 20 junior high school counselors in Malang City. The outcome of this program is demonstrated by an increase in the partners' competencies in conducting behavior analysis and modification, as indicated by higher post-test scores. Abstrak: Pengabdian pada masyarakat ini merupakan penerapan hasil penelitian tentang pengembangan model program peningkatan kompetensi konselor melalui analisis dan pengubahan tingkah laku pada siswa SMP kota Malang. Model ini dirancang untuk memberikan pelatihan dan pendampingan pelaksanaan program analisis dan pengubahan tingkah laku bermasalah siswa, serta memberikan panduan dan rekomendasi perbaikan. Pelatihan dilaksanakan menggunakan metode Problem Based Learning (PBL), dengan prosedur : (1) persiapan, (2) pelaksanaan, (3) evaluasi dan follow-up, (4) pelaporan. Sasaran program peningkatan kompetensi konselor terdiri atas 20 konselor SMP di Kota Malang. Hasil dari pelaksanaan program ini berupa peningkatan kompetensi mitra dalam melaksanakan analisis dan pengubahan tingkah laku yang ditunjukkan dengan peningkatan skor posttest.